2019
DOI: 10.33007/inf.v5i2.1728
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Kemitraan Pemerintah Dan Swasta Dalam Upaya Penanggulangan Kemiskinan: Sebuah Tinjauan Literatur

Abstract: Kemiskinan merupakan salah satu permasalahan terbesar di dunia. Permasalahan tersebut membutuhkan solusi yang komprehensif. Salah satu alternatif yang dapat dilakukan untuk menanggulangi kemiskinan yaitu dengan melakukan kemitraan antara pemerintah dan swasta (public-private partnership). Pada dasarnya, kemitraan yang dilakukan antara pemerintah dan swasta berdampak pada efektivitas upaya penanggulangan kemiskinan, meskipun berbagai permasalahan dan kendala kerap ditemui dalam pelaksanaan kemitraan tersebut. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Administrasi Publik juga harus dilakukan dengan memperhatikan prinsip-prinsip akuntabilitas, transparansi, dan partisipasi publik. Hal ini akan memastikan bahwa kebijakan yang diambil oleh pemerintah dapat dipertanggungjawabkan dan dapat diterima oleh masyarakat (Rasdi & Kurniawan, 2019). Secara keseluruhan, Administrasi Publik merupakan suatu kegiatan yang sangat penting dalam menjalankan fungsi-fungsi pemerintah dan memenuhi kebutuhan masyarakat.…”
Section: Administrasi Publikunclassified
“…Administrasi Publik juga harus dilakukan dengan memperhatikan prinsip-prinsip akuntabilitas, transparansi, dan partisipasi publik. Hal ini akan memastikan bahwa kebijakan yang diambil oleh pemerintah dapat dipertanggungjawabkan dan dapat diterima oleh masyarakat (Rasdi & Kurniawan, 2019). Secara keseluruhan, Administrasi Publik merupakan suatu kegiatan yang sangat penting dalam menjalankan fungsi-fungsi pemerintah dan memenuhi kebutuhan masyarakat.…”
Section: Administrasi Publikunclassified
“…This condition increases government spending through investment, training, and skills programs to encourage people to be able to manage their income (Saputra and Ali, 2022). However, developing community skills to support the sustainability of the green economy cannot be done instantly, so large investment expenditures are required (Rasdi, 2020). Sustainable subsidies for the poor are very vulnerable to conditions in countries that are not ready to maintain the desire for a green economy (Hardianto and Desa, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of poverty has never been resolved every year, so the government has the duty and responsibility to overcome the poverty problems that occur. As with the poverty problems that occur in Indonesia in the field of education, it was found that children who were in compulsory school age chose not to go to school due to limited costs, besides that it was also found that children of compulsory school age chose to work rather than go to school to meet their daily needs (Aini & Islamy, 2021;Rasdi & Kurniawan, 2018). The problem of poverty needs to be minimized by the government, one of the things Lia Mita Syahri / Existential Logotherapy in Improving the Meaningfulness of Life of Pre-Prosperous Family Students the government has done in overcoming the high poverty rate is to provide tuition assistance called PIP.…”
Section: Introductionmentioning
confidence: 99%